The fiscal capacity of local government versus government expenditure, and its impact on eliminating interregional social inequalities in Poland - Małgorzata Gałecka; Leszek Patrzałek; Ireneusz Kuropka; Ewa Szabela-Pasierbińska (REGION, 2022)
Social inequalities are a significant challenge in developing countries. Therefore, they should be treated as a leading priority in boosting socio-economic development. Such inequalities are a growing challenge for Poland. It is believed that social inequalities are behind Poland's relatively low position against other European countries in the Human Development Index ranking. Many factors influence social inequalities, one being the system of financing local government units. A critical area for considering social inequalities in the context of financial phenomena is the study of fiscal inequalities resulting from the implemented vertical division of public revenues among individual levels of public authority. The paper presents the results of research on the relationship between the fiscal capacity of local government units in Poland across voivodeships and the expenditure of government institutions, as well as the relationship of these expenses with social inequalities in voivodeships. To this end, six areas of social life were distinguished, for which the degree of inequality of transferred expenditure was determined using the Gini index. The method of the total order of objects was used to assess the impact of government institutions' expenditure on an individual's social situation across voivodeships. The conducted research showed both the weak dependence of government expenditure on individual units' fiscal capacity and its low effectiveness in eliminating inter-voivodeship social inequalities.
Keywords: H20; H5; H70; R12; 330; fiscal capacity; tax capacity; local government units; social inequalities; interregional diversity